2008
DOI: 10.1007/s00044-007-9081-0
|View full text |Cite
|
Sign up to set email alerts
|

Radical scavenging capacities of some thiazolylthiazolidine-2,4-dione derivatives

Abstract: In this study, a series of 2,4-dichlorothiazolyl thiazolidine-2,4-dione (Iaf) and 4-chloro-2-benzylsulfanylthiazolyl-thiazolidine-2,4-dione derivatives (IIa-f) were tested for their antioxidant properties by determining their effects on superoxide anion formation, and the 2,2-diphenyl-1-picrylhydrazyl (DPPH) stable free radical. Compound Ic showed the best superoxide anion scavenging activity at the 10 -3 M and 10 -4 M concentrations. The compounds (Ia-f and IIa-f) had the strong DPPH radical scavenger capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Indeed, taking folic acid as an example, the reactivity toward H 2 DCFDA was clearly reduced when using the thiazolidine CP compared with pyruvate alone. This higher efficacy of thiazolidines to inhibit the reactivity of single and combined components is probably linked to a capacity to scavenge other radicals like HO• and O 2 •− as demonstrated for chromonyl‐thiazolidine‐2,4‐dione or for several other thiazolidine derivatives . Since folic acid is sensitive to H 2 O 2 and HO•, the fact that thiazolidines scavenge hydroxyl radicals may explain the stabilization effect on this vitamin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, taking folic acid as an example, the reactivity toward H 2 DCFDA was clearly reduced when using the thiazolidine CP compared with pyruvate alone. This higher efficacy of thiazolidines to inhibit the reactivity of single and combined components is probably linked to a capacity to scavenge other radicals like HO• and O 2 •− as demonstrated for chromonyl‐thiazolidine‐2,4‐dione or for several other thiazolidine derivatives . Since folic acid is sensitive to H 2 O 2 and HO•, the fact that thiazolidines scavenge hydroxyl radicals may explain the stabilization effect on this vitamin.…”
Section: Discussionmentioning
confidence: 98%
“…This higher efficacy of thiazolidines to inhibit the reactivity of single and combined components is probably linked to a capacity to scavenge other radicals like HO• and O 2 •2 as demonstrated for chromonyl-thiazolidine-2,4-dione 41 or for several other thiazolidine derivatives. 32,42,43 Since folic acid is sensitive to H 2 O 2 and HO•, the fact that thiazolidines scavenge hydroxyl radicals may explain the stabilization effect on this vitamin. Furthermore, investigations of several synthesized 2-aryl thiazolidine-4-carboxylic acid revealed that the antioxidant activity of this class of molecules may be attributed to the presence of the oxidizable sulfur in the thiazolidine ring.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant properties of a series of 2,4dichlorothiazolylthiazolidine-2,4-dione and 4-chloro-2benzylsulfanylthiazolyl-thiazolidine-2,4-dione derivatives 179 (Scheme 86) were reported in two different in vitro assays: superoxide anion radical formation and DPPH radical scavenging activity [408].…”
Section: Anti-and Prooxidant Agentsmentioning
confidence: 99%
“…Thiazolidine-2,4-dione derivatives have been studied extensively and found to have diverse chemical reactivity (Jain et al, 2013;Faiyazalam et al, 2013). Thiazolidine derivatives displayed a broad spectrum of biological activities including antimicrobial (Gouveia et al, 2009;Tuncbilek and Altanlar, 2006), antidiabetic (Murugan et al, 2009;Pattan et al, 2005), antiobesity (Bhattarai et al, 2009), anti-inflammatory (Youssef et al, 2010), antioxidant (Bozdag-Dundar et al, 2009), antiproliferative (Patil et al, 2010), and antitumor (Shimazaki et al, 2008). They inhibit corrosion of mild steels in acidic solution (Donnelly et al, 1974).…”
Section: Introductionmentioning
confidence: 97%